Use of conservative therapy before and after surgery for carpal tunnel syndrome - Multanen, Juhani; Uimonen, Mikko M.; Repo, Jussi P.; Häkkinen, Arja; Ylinen, Jari (BMC musculoskeletal disorders, 2021)
Background Conservative therapies are typically offered to individuals who experience mild or intermittent symptoms of carpal tunnel syndrome (CTS) or postoperatively to subjects who have undergone carpal tunnel release. Although long-term studies report mostly positive results for carpal tunnel release, knowledge on the need for conservative treatments following surgery is scarce. The aim of this retrospective cohort study was to examine the use of conservative therapies before and after carpal tunnel releasing surgery. Methods Of 528 patients who underwent carpal tunnel release surgery in the study hospital during the study period, 259 provided sufficiently completed questionnaires (response rate 49 %). The patients completed a questionnaire battery including a sociodemographic, medical history and symptom questionnaire, the Boston Carpal Tunnel Syndrome Questionnaire, 6-item CTS symptoms scale and EuroQoL 5D. Frequencies of conservative therapies pre- and postoperatively were calculated. Association between Pain VAS and satisfaction with treatment were examined in patient groups according to the use of conservative therapies. Results Of all patients, 41 (16 %) reported receiving only preoperative, 18 (7 %) reported receiving only postoperative, 157 (60 %) reported receiving both pre- and postoperative conservative therapies and 43 (17 %) did not receive any therapies. Preoperative use of conservative therapies was more common in females than males (82 % vs. 64 %; p = 0.002), but postoperatively no significant gender difference was observed. The patients who received conservative therapies were younger than non-users in both the preoperative (median age 59 vs. 66; p < 0.001) and postoperative (59 vs. 66; p = 0.04) phases. The patients reported high satisfaction with their treatment and simultaneous improvement in Pain VAS scores. Those receiving conservative therapies only preoperatively reported the highest satisfaction. Conclusions While the use of conservative therapies decreased after surgery, a large proportion of the patients received these adjunct interventions. Patients reported high satisfaction with their treatment one year post surgery. Pain outcome seems to be closely related to satisfaction with treatment. Level of Evidence Level III.